Nursing care for people with Chagas disease: a scoping review - Silva Júnior, José Antonio da; Duarte Fonseca, Álvaro Micael; Andrade, Micássio Fernandes de; Andrade, Cléber de Mesquita; Santos, Ísis Kelly dos; Cosme do Nascimento, Ellany Gurgel (Revista Cuidarte, 2024)
Highlights • There is little scientific evidence about Chagas disease and nursing care, most of the scientific evidence found was carried out in the Latin American region. • By summarizing the findings in the scientific literature, we can begin to understand the problem of Chagas disease and its care by nursing. • We can identify the main nursing care already developed for people with Chagas disease and the potential for future clinical research. • The findings of this study elucidate nursing knowledge in Brazil and in the world about care for people with Chagas disease; Understanding aspects of care for these people is necessary to identification self-care capacity and the needs of nursing interventions. Introduction: Chagas disease is an infectious disease caused by the parasitism process of the protozoan Trypanosoma cruzi. Given its potential for chronicity, nursing care in the health care of patients with Chagas disease will provide an improvement in quality of life and the prognosis of the disease. Objective: Review scientific knowledge about nursing care for individuals with Chagas disease. Material and Methods: descriptive and exploratory research, carried out with two independent reviewers using high sensitivity criteria in databases and gray literature sources between June and July 2022. Results: The review identified 12 relevant publications that emphasized health care, education, relationships, disease prevention and health promotion. The most frequent and diverse nursing diagnoses were related to the Activity/Rest, Health Promotion and Coping/Stress domains. Discussion: To meet the care needs of Chagas disease, it is essential to ensure nursing care that recognizes individualities, highlighting the importance of creating tools that facilitate the nursing process. The main points highlighted were related to the health education process, longitudinal monitoring, healthy lifestyle habits, general nursing care during hospitalization and the use of nursing diagnoses. Conclusion: the need for comprehensive nursing care that meets the main needs of individuals with Chagas disease is emphasized, considering their unique circumstances. Developing tools to support the nursing process is essential to improve the results of care for this population. How to cite this article: Silva Júnior, José Antonio da; Fonseca, Álvaro Micael Duarte; Andrade, Micássio Fernandes de; Andrade, Cléber de Mesquita; Santos, Isis Kelly dos; Nascimento, Ellany Gurgel Cosme do. Nursing care for people with Chagas Disease: a scoping review. Revista Cuidarte. 2024;15(1):e3420. http://dx.doi.org/10.15649/cuidarte.3420